2013
DOI: 10.4238/2013.december.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' tumor suppressor gene mutations in girls with sporadic isolated steroid-resistant nephrotic syndrome

Abstract: ABSTRACT. Mutations in the Wilms' tumor suppressor gene (WT1) can lead to syndromic forms of steroid-resistant nephrotic syndrome (SRNS) such as Denys-Drash or Frasier syndrome and can cause isolated SRNS. A mutation within WT1 is a frequent cause of sporadic isolated SRNS in girls. In a worldwide cohort of girls, the rate of occurrence was 10.8%. Previous reports have indicated that in Chinese girls, the detection rate of WT1 mutations is 16.7% for early onset isolated nephrotic syndrome. The detection rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Interestingly, one unusual FS case was reported with an IVS 9 + 4 C>T mutation, genotypically the case was a male and presented with diaphragmatic hernia, hypospadias and unilateral cryptorchidism23. According to the reports, WT1 mutation mostly occurred in SRNS girls71011121324. Early (pre-pubertal period) diagnosis may help in the management of FS and to offer a reliable prognosis11121922.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, one unusual FS case was reported with an IVS 9 + 4 C>T mutation, genotypically the case was a male and presented with diaphragmatic hernia, hypospadias and unilateral cryptorchidism23. According to the reports, WT1 mutation mostly occurred in SRNS girls71011121324. Early (pre-pubertal period) diagnosis may help in the management of FS and to offer a reliable prognosis11121922.…”
Section: Resultsmentioning
confidence: 99%
“…Eight cases of type 3 Frasier syndrome have been reported (10,13,14,(31)(32)(33)(34)(35)(36). Few type 3 Frasier syndrome cases are diagnosed because patients exhibit normal secondary sexual characteristics by the XX chromosome and suffer from renal failure without gonadal impairment.…”
Section: Type 3 Frasier Syndrome (Female External Genitals With Sex Cmentioning
confidence: 99%
“…Recent studies have demonstrated that mutations in WT1 can lead to syndromic forms of steroid-resistant NS (SRNS), such as Denys-Drash or Frasier syndrome, and can cause isolated SRNS [8, 9]. Between 10% and 20% of patients fail to respond to steroid therapy; thus, the prognosis for SRNS is usually poor, due to the increased risk of developing end-stage renal disease [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Beltcheva et al reported a case of a pediatric patient with SRNS that was caused by a novel dominant WT1 mutation, C11184A, identified in exon 9 [10]. Mutations within WT1 are frequent causes of sporadic, isolated cases of SRNS in girls [8]. WT1 expression is modulated by microRNAs (miRNAs) [12], which are small (20–25 nucleotides), noncoding RNA molecules that act as posttranscriptional regulators of gene expression in animals and plants, participating in many key biological processes [13].…”
Section: Introductionmentioning
confidence: 99%